Capillary electrophoresis in an extended nanospray tip-electrospray as an electrophoretic column - Tycova, Anna; Foret, Frantisek (Journal of chromatography. A, 2015)
Capillary electrophoresis coupled to mass spectrometry (CE/MS) is gaining its space among the most powerful tools in modern (bio)analytical laboratory. The most challenging instrumental aspect in CE/MS is striking the balance between the stability and reproducibility of the signal and sensitivity of the analysis. Several interface designs have been published in the past decade addressing the variety of instrumental aspects and ease of operation. Most of the interfaces can be categorized either into the sheath flow arrangement (considered to be a de facto standard), or sheathless interface, often expected to provide the ultimate sensitivity. In this work we have explored an "interface-free" approach, where the CE/MS analysis was performed in narrow bore (<20 μm ID) electrospray capillary. The separation capillary and electrospray tip formed one entity and the high voltage, applied at the injection end of the capillary served for both the separation and electrospray ionization. Thus the separation voltage was defined as the product of the electrospray current and resistivity of the separation electrolyte. Optimum conditions for the separation and electrospray ionization were achieved with voltage programming. The performance of this simplest possible CE/MS system was tested on peptide separations from the cytochrome c tryptic digest. The subnanoliter sample consumption and sensitivity in the attomole range predetermines such a system for analysis of limited samples.
Keywords: Reproducibility of Results; peptidové fragmenty; Capillary electrophoresis; Separation; hmotnostní spektrometrie s elektrosprejovou ionizací; lidé; reprodukovatelnost výsledků; cytochromy c; Cytochromes c; Mass spectrometry; Nanospray; Electrophoresis, Capillary; Peptide Fragments; Spectrometry, Mass, Electrospray Ionization; Interface; elektroforéza kapilární; Humans